The Effects of Using Seaweed (E. Cottonii) on Physical Quality and Organoleptic of Chicken Nuggets (Jurnal Ilmu dan Teknologi Hasil Ternak, 2008)
This research was experimental method with Completely Random Design.  Seaweed used to chicken nuggets in the vary concentration, namely: 0% (F0), 10% (F1), 20% (F2), 30% (F3), 40% (F4). The observed variables were texture, water holding capacity (WHC), pH, and organoleptic quality of chicken nuggets. Collected data were analyzed using analisys variation method and followed by Duncan analysis if the result on the previous analysis showed significant difference. The  result  showed  that  chicken  nuggets  using  seaweed  gave highly significant effect  (P<0.01) on  texture, WHC, pH, and   organoleptic quality. The best result was chicken nuggets made with used of seaweed  10%;  7.97 N of texture; 4.50% of WHC; 6.16 of pH; 6.98 of texture organoleptic score; and 6.26 of taste organoleptic score. The conclusion of this research was the using of seaweed to chicken nuggets gave a significant effect on  texture, WHC, pH, and organoleptic quality. Based on the result, it suggested that using 10% of seaweed to make chicken nugeets.   Keyword : water holding capacity, chicken nuggets, seaweed